INFORMATION NEEDS OF MUSHROOM CULTIVATORS IN UDHAM SINGH NAGAR DISTRICT OF UTTARAKHAND - ARPITA SHARMA* (The Journal of Research ANGRAU, 2021)
The study was conducted to identify the needs of the mushroom cultivators. Seven villageswere selected randomly and 100 respondents were selected. A list of 10 major areas of needs inrelation to improved package of practices of mushroom cultivation was prepared. The collection ofinformation is completed by pre-tested questionnaire. The study revealed that majority of mushroomgrowers were middle aged (45 percent) and possess secondary education (37 percent). The majorsources of information were cell phone and T.V and majority have access to WhatsApp (social media)on their phones. The overall need assessment depicted that the training required of the mushroomgrowers was high especially regarding cultivation of mushroom, crop management, spawn preparationand the other procedures.